ORGANIZATION OF SCIENTIFIC-COGNITIVE EXCURSION ROUTES AS A FACTOR OF ECOLOGICAL EDUCATION OF STUDENTS IN MOUNTAIN SCHOOLS - Gniezdilova, Victoria; Buniak, Vira; Lysiuk, Iryna (Mountain School of Ukrainian Carpaty, 2021)
Excursions to nature with students of different ages contribute to the intensification of the educational process, create conditions for the organization of independent work of students. By paving ecological trails, students have the opportunity to get acquainted with various biocenoses and their species composition, to see connections in plant groups, their seasonal changes, to study the most typical ecological objects related to the impact of human activities. Everything that contributes to the formation of students’ ecological culture, reveals the worldview of modern environmental issues. The aim of our work was to study the organization of scientific and cognitive ecological trails in natural landscapes and complexes. The article presents the results of a study conducted on the basis of mountain rural schools in Zakarpattia and Ivano- Frankivsk regions. Two scientific and cognitive ecological trails were designed and organized with the members of the botanical and naturalistic circle of Tereblyansky Educational Complex: "In the native Tereblyanska side" and "Shirokoluzhansky nature reserve as a standard of beech virgin Carpathian forests". The first of them is of local lore nature, and the second is devoted to the study of the vegetation of the Carpathian Biosphere Reserve. The students of Perehinskyi Educational Complex developed the ecological trail "Vegetation of the mountain banks of Limnytsia - a valuable botanical gene pool of the Carpathians".